Practical Stability in the $p$th Mean of Stochastic Differential Equations with Discontinuous Coefficients (Communications in Mathematical Research, 2021)
In this paper, we give sufficient conditions to analyze the practical stability in the $p$th mean of stochastic differential equations with discontinuous coefficients.The Lyapunov-like function plays an important role in analysis. Some numerical computations are carried out to illustrate the theoretical results.
Keywords: stochastic differential equation; practical stability in the $p$th mean; Lyapunov-like function.